Previsão de consumo de médio e longo prazo - André Marques Rodrigues (2021)
Medium and long term load forecasting has great influence over the planning and expansion of the electric energy systems. The purpose of this paper is to forecast the global load of three european countries: Portugal, Spain and France, focusing more on the distribution of the hourly load across each year. The paper will focus on the impact of several factors that affect the load like: season of the year, weekday, holidays, temperature and others. This work is based on real life data.